Eficiência relativa das filiais de uma cooperativa de agronegócios: estudo dos fatores internos e externos utilizando a análise envoltória de dados - Leal, Francisco Cezar dos Reis (Universidade do Vale do Rio dos Sinos, 2013)
This study evaluates the internal and external elements that may compromise the efficiency of the branches of a cooperative agribusiness located in the southern region of Brazil, and, therefore, establish criteria and models that distinguish efficient operations from inefficient operations. The study is contextualized on the history of cooperatives, as well as their representation within the current economic outlook and the Brazilian agribusiness. Given the objective of this study, after performing statistical analyzes of correlation, we used the methodology of Data Envelopment Analysis (DEA) to generate the scores and identify efficient units arising from its internal elements. Therefore, we used the external variables with the scores resulting from the DEA to evaluate the impact of these external factors on predicting the internal efficiency of the cooperative units, using regression analysis. The study revealed that the external variable that has the greatest impact on the efficiency of the units of the relation to the scores presented is the municipal Gross Domestic Product, followed by the Gross Value Added of Agriculture and Rural Population Segment, which proved to be significant according to the results presented in the analysis. Likewise, the most descriptive internal variables (inputs and outputs) for representing the efficient frontier (44.4% of the units) are Potential Revenue, Number of Employees and Associates.
Keywords: Cooperativismo; Análise envoltória de dados; Eficiência; Cooperativas; Cooperatives; Data envelopment analysis; Efficiency; ACCNPQ::Engenharias::Engenharia de Produção